Digital Promotion, Service Quality, and Sustainable Performance: An Empirical Study of an Indonesian Pet Shop SME - Dea Nabila Putri; Desma Erica Maryati; Lisa Elianti Nasution (Yayasan Sembilan Pemuda Indonesia, 2026)
This study aims to analyze the effect of digital promotion and service quality on sustainable performance in Small and Medium Enterprises (SMEs) at Sinar Jaya Petshop in Indonesia. The study uses a quantitative approach with a survey design, as well as purposive sampling technique on 70 respondents who are store customers. Data were collected through a questionnaire using a Likert scale and analyzed using multiple linear regression. The results of the study indicate that digital promotion and service quality, both partially and simultaneously, have a positive and significant effect on sustainable performance. This shows that improving digital promotion strategies and service quality can drive an increase in sustainable business performance. However, the coefficient of determination (R²) value of 0.140 indicates that the model's ability to explain variations in sustainable performance is still limited, so there are other factors outside the model that also influence it. Therefore, business actors are advised not to focus solely on digital promotion and service quality, but also to consider other factors such as innovation, price, and customer loyalty to optimally improve sustainable performance.